Reliability and lifetime of lithium disilicate, 3Y-TZP, and 5Y-TZP zirconia crowns with different occlusal thicknesses - Adabo, Gelson Luis [UNESP]; Longhini, Diogo [UNESP]; Baldochi, Mariana Ribeiro [UNESP]; Bergamo, Edmara Tatiely Pedroso; Bonfante, Estevam Augusto (Springer Nature, 2023)
Objectives: To assess the probability of survival of crowns made with a 3Y-TZP, a 5Y-TZP, and a lithium disilicate. Materials and methods: CAD-CAM premolar crowns with occlusal thicknesses of 1.0 mm or 1.5 mm and cemented on a metal dye. Step-stress accelerated life testing (SSALT) was performed to access the use level probability Weibull curves and reliability were calculated for the completion of a mission of 100,000 cycles at 300 to 1200 N. Results: All ceramics showed a high probability of survival (87–99%) at 300 N, irrespective of thickness. 3Y-TZP shows no significant decrease in the probability of survival up to 1200 N (83–96%). Lithium disilicate presented lower reliability than zirconia under the 600 N mission. 5Y-TZP showed lower reliability than 3Y-TZP at 1200 N. There was no significant difference in the Weibull modulus (3.23–7.12). 3Y-TZP had the highest characteristic strength (2483–2972 N), followed by 5Y-TZP (1512–1547 N) and lithium disilicate (971–1154 N). Conclusion: Zirconia ceramics have a high probability of survival (up to 900 N-load), while lithium disilicate survives up to 300 N load only, irrespective of the thickness (1.0 mm or 1.5 mm). Clinical relevance: The probability of survival of posterior crowns made with zirconia ceramics resists extreme loads while glass ceramics resist normal chewing loads. In addition, crowns with thinner occlusal face showed sufficient mechanical behavior.
Keywords: Biaxial flexural strength; Ceramics; Fully stabilized zirconia; Lithium disilicate; Material resistance; Monolithic zirconia; Partially stabilized zirconia